Emerging Influenza D virus infection in European livestock as determined in serology studies: Are we underestimating its spread over the continent?. Issue 3 (18th September 2020) - Gaudino, Maria; Moreno, Ana; Snoeck, Chantal J.; Zohari, Siamak; Saegerman, Claude; O'Donovan, Tom; Ryan, Eoin; Zanni, Irene; Foni, Emanuela; Sausy, Aurelie; Hübschen, Judith M.; Meyer, Gilles; et al.
Abstract: Influenza D virus (IDV) is a novel orthomyxovirus that was first isolated in 2011 in the United States from a swine exhibiting influenza‐like disease. To date, its detection is extended to all continents and in a broad host range: IDV is circulating in cattle, swine, feral swine, camelids, small ruminants and horses. Evidence also suggests a possible species jump to humans, underlining the issue of zoonotic potential. In Europe, serological investigations in cattle have partially allowed the understanding of the virus diffusion in different countries such as Italy, France, Luxembourg and Ireland. The infection is widespread in cattle but limited in other investigated species, consolidating the assumption of cattle as IDV primary host. We hypothesize that commercial livestock trade could play a role in the observed differences in IDV seroprevalence among these areas. Indeed, the overall level of exposure in cattle and swine in destination countries (e.g. Italy) is higher than in origin countries (e.g. France), leading to the hypothesis of a viral shedding following the transportation of young cattle abroad and thus contributing to larger diffusion at countries of destination. IDV large geographic circulation in cattle from Northern to more Southern European countries also supports the hypothesis of a viral spread through livestock trade. This review summarizes available data on IDV seroprevalence in Europe collected so far and integrates unpublished data from IDV European surveillance framework of the last decade. In addition, the possible role of livestock trade and biosecurity measures in this pathogen's spread is discussed.